Severity and Pattern of Coronary Artery Disease in Patients with Cardiovascular Dysmetabolic Syndrome - Jamil, AA; Haque, KMHSS; Mamun, AA; Siddique, MA; Banerji, SK; Jaman, SMM; Islam, MN; AHmed, QS; Rahman, SMM (Nepalese Heart Journal, 2004)
A cross-sectional study was carried out in the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka in collaboration with Department of Cardiology, CMH, Dhaka Cantonment from June 1999 to May 2000. The patients clinically diagnosed or documented to have coronary artery disease (CAD) requiring coronary angiography (CAG) were included in the study, and were grouped into patients with Cardiovascular Dysmetabalic Syndrome (CDS Group) and without CDS (non-CDS group). The CDS was diagnosed by using the diagnostic criteria defined by Western Working Group, Hawaii, in 1997, Patients with hypertrophic and dilated cardiomyopathies, valvular and congenital heart diseases, and other systemic diseases were excluded frarn the study. OtherCAD risk factors, i,e. Smoking, family history of CAD and physical inactivity were also analyzed. The CAG findings were analyzed in terms of severity and pattern of coronary lesions and were compared between the groups.